2013
DOI: 10.1111/jam.12235
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth media and physical treatments on the adhesion properties of canine probiotics

Abstract: Aims: The manufacturing processes have been reported to influence the properties of probiotics with potential impact on health properties. The aim was to investigate the effect of different growth media and inactivation methods on the properties of canine-originated probiotic bacteria alone and in combination mixture. Methods and Results: Three established dog probiotics, Lactobacillus fermentum VET9A, Lactobacillus plantarum VET14A and Lactobacillus rhamnosus VET16A, and their combination mixture were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…We have recently demonstrated that these same probiotic bacteria of canine origin present different adhesive properties when cultivated in different media and inactivated by different treatments (Grześkowiak et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We have recently demonstrated that these same probiotic bacteria of canine origin present different adhesive properties when cultivated in different media and inactivated by different treatments (Grześkowiak et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Vahjen and Manner ; Grześkowiak et al . ). Our results show that all the pathogens tested have the ability to bind to intestinal mucus, which thus benefits the pathogens in invading the host.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations